Trends and Issues in Global Tourism 2007 - Conrady, Roland; Buck, Martin (Trends and Issues in Global Tourism, 2007)
As other industries, the global travel and tourism industry has been facing - mense challenges and highly visible upheaval since the beginning of the new m- lennium. The International Tourism Exchange ITB Berlin, the world's leading travel trade fair, aims at pinpointing the most important challenges, identifying the trends and offering a platform to solve pressing problems. The ITB Convention Market Trends & Innovations has developed into a center of excellence and a driving force for the global travel and tourism industry, generating a much needed information platform. This compilation unites the highlights of the convention in articles prepared by renowned professionals and scientists from the industry. Readers may benefit from this comprehensive vision of the developments which are shaping the str- ture of the global tourism industry today and in the future. This book is indisp- sable for tourism and travel professionals and well as for academics and students analyzing current global tourism and travel trends. The first chapter takes up the issue of mega trends in society and in the ec- omy and analyzes their effects on the tourism industry. In highly developed co- tries, overwhelming demographical change is underway. Schröder and Widmann demonstrate how tourism businesses should adapt to the aging customer base.